The Efficacy of Counseling Interventions in Addressing Domestic Violence Among Young Adult Couples: A Case Study of Kauga Sub-county, Mukono District - Joy Lynn Tusiime (Uganda Christian University, 2024)
This research report was undertaken to investigate on the efficacy of counseling interventions in addressing domestic violence among young adult couples in Kauga sub-county, mukono district. It was guided by three objectives; to examine the effect of psycho education on addressing domestic violence among young adult couples in kauga sub-county, to analyze on the effect of cognitive-behavioral interventions on addressing domestic violence among young adult couples in kauga sub-county, to determine the effect of supportive counseling on addressing domestic violence among young adult couples in kauga sub-county.
Research
The efficacy of counseling interventions in addressing domestic violence among young adult couples partially depends on their ability to provide the necessary structure, support, and guidance to those experiencing abusive behaviors. Specifically, counseling interventions, such as cognitive-behavioral therapy and relationship counseling, help the individuals and couples to recognize and change patterns of behavior that harm others, improve their communication skills, and develop more adequate coping strategies.